Method of Quantitative Measurement of Human Platelet Aggregation in Clinical Practice - Sakurai, Izo; Otsuka, Kazuoki; Satoh, Tsunehisa (Nihon Rōnen Igakkai zasshi, 1998)
We examined the quantitative measurement of platelet aggregation in 20 volunteers and 89 patients with ischemic heart disease (IHD). Subjects in whom platelet aggregation was induced by an adenosine diphosphate (ADP) and an epinephrine solution were clearly divided into two groups: “normal” and “accentuated”. We chose the maximum aggregation time for the ADP solution and the maximum transmission rate for the epinephrine solution for the quantitative measurement of platelet aggregation. The results were as follows. The maximum aggregation time with a 1.0μM ADP solution in the normal group of 13 volunteers was 0.71±0.12min, (mean±SD), in 50 IHD patients it was 0.91±0.49min, in the “accentuated” group of 7 volunteers it was 5.34±1.18min, in 39 IHD patients it was 6.01±1.22min. The maximum light transmission rate with a 0.1μM epinephrine solution in the normal group of 14 volunteers was 8.04±4.14%, in 52 IHD patients it was 13.74±5.75%, in the “accentuated” group of 6 volunteers it was 76.33±9.91%, and in 37 IHD patients it was 77.26±13.39%. The difference between the“normal” and “accentuated” groups was statistically significant (p<0.001), with the ADP and with the epinephrine solution. Next, we examined the effect of antiplatelet therapy (dipyridamole and aspirin) on 15 patients selected from among those with IHD who had accentuated platelet aggregation when the ADP solution was added. Their maximum aggregation time was 5.98±1.24min, and their maximum platelet aggregation rate when the epinephrine solution was added was 78.90±11.60% (10 patients), 20.00±3.24% (5 patients). After the therapies, the maximum aggregation time in 10 patients was 0.94±0.21min (return to normal condition), and in 5 patients it was 5.90±1.09min (not effective). The maximum platelet aggregation rate in 10 patients was 14.11±5.88% (normal condition), and in 5 patients it was 75.00±9.51% (not effective). Finally, we examined the long term effects of various antiplatelet drugs. Most of the patients in whom platelet aggregation was accentuated got well.